Persistence of measles, mumps, and rubella protective antibodies 3 years after revaccination in HIV-infected children receiving antiretroviral therapy - Aurpibul L. (2014)
Three years after measles, mumps, and rubella revaccination in 38 human immunodeficiency virus-infected children who had achieved immune recovery after antiretroviral therapy, the prevalence of protective antibody levels was 85% for measles, 61% for mumps, and 79% for rubella, compared with 88%, 84%, and 100%, respectively, 1 month after revaccination. © 2010 by the Infectious Diseases Society of America. All rights reserved.